2021
DOI: 10.3390/plants10050939
|View full text |Cite
|
Sign up to set email alerts
|

Root System Architecture Plasticity of Bread Wheat in Response to Oxidative Burst under Extended Osmotic Stress

Abstract: There is a demand for an increase in crop production because of the growing population, but water shortage hinders the expansion of wheat cultivation, one of the most important crops worldwide. Polyethylene glycol (PEG) was used to mimic drought stress due to its high osmotic potentials generated in plants subjected to it. This study aimed to determine the root system architecture (RSA) plasticity of eight bread wheat genotypes under osmotic stress in relation to the oxidative status and mitochondrial membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…: 251520, Sigma-Aldrich Chemical Co., St. Louis, MO, USA). DCFH-DA (0.25 µM) in 1x PBS buffer solution was used as described by Azab et al [22]. After 30 min of incubation, the roots were washed twice with PBS buffer and imaged using a fluorescence microscope (Nikon Eclipse 80i, Tokyo, Japan) and with filter set 10 (excitation 485 nm; emission: 530 nm).…”
Section: Rsa Trait Measurements For Wt Plants and Transgenic Tobacco ...mentioning
confidence: 99%
See 1 more Smart Citation
“…: 251520, Sigma-Aldrich Chemical Co., St. Louis, MO, USA). DCFH-DA (0.25 µM) in 1x PBS buffer solution was used as described by Azab et al [22]. After 30 min of incubation, the roots were washed twice with PBS buffer and imaged using a fluorescence microscope (Nikon Eclipse 80i, Tokyo, Japan) and with filter set 10 (excitation 485 nm; emission: 530 nm).…”
Section: Rsa Trait Measurements For Wt Plants and Transgenic Tobacco ...mentioning
confidence: 99%
“…Our previous study showed that an adapted root in wheat (Triticum aestivum) was correlated with high antioxidant ability [22]. The R2R3-MYB TaMYB20 was found to be a key factor in drought tolerance [23] and to display antioxidant activity preventing oxidative damage [19].…”
Section: Introductionmentioning
confidence: 99%
“…The experiment consisted of three treatments (control, S1 and S2) with three replicates for each genotype. The sampling of roots was carried out by randomly selecting one seedling from each genotype from each box; toluidine red was used to stain the roots, as described by [29]. Then, the roots were spread on a glass sheet, and the excess staining solution was removed carefully using tissue paper.…”
Section: Rsa Trait Measurementsmentioning
confidence: 99%
“…Functionally, plant roots are characterized by the presence of a meristematic and elongation zone, in which the rate of cell division is high and reactive oxygen species (ROS) serve as signaling molecules, which is the same as the functional role of hormones [28]. The overproduction of ROS is potentially harmful as they are regarded as the regulators of cellular component damage and irreparable metabolic dysfunction, which consequently results in mitochondrial dysfunction and programed cell death [29]. The enzymatic activity of superoxide dismutase in wheat plants results in primary root elongation under osmotic stress [30].…”
Section: Introductionmentioning
confidence: 99%